Assessing financial health in small businesses: a structural equation modeling study (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Small business financial health evaluation is a crucial yet challenging process that affects sustainability, performance, and decision-making. In this study, structural equation modeling (SEM) is used to look at the many different aspects that affect small enterprises' financial health. We examine the interactions between financial metrics, operational effectiveness, strategic management approaches, and external environmental variables using a large dataset of small businesses. Our findings illustrate the complex web of factors on financial health by revealing strong connections between these latent dimensions. The SEM framework facilitates in estimating the relative impacts of the variables by illuminating their direct and indirect interactions. The study also sheds light on the particular difficulties encountered by small enterprises and the need of specialized financial evaluation.
Keywords: Financial health; Small business; SEM